The State of Psychoemotional, Cytokine Status and Endothelial Function in Patients with Combined Surgical Pathology of the Abdominal Cavity, True Pelvis and Anterior Abdominal Wall, Depending on the Methodic of Simultaneous Surgical Intervention - Gumenyuk, Lesya N.; Gerbali, Oksana Yu.; Mykhaylichenko, Vyacheslav Yu. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The relevance of the study is in the fact that disorders of vascular and psychoneuroendocrine genesis often accompany surgical diseases, the issue of ensuring patient safety in the perioperative period remains the basic focus of modern clinical surgery. The purpose of the study is to identify changes in the level of pro-inflammatory cytokines and the functional state of the endothelium, and also to establish whether the transferred simultaneous surgical interventions intensified pro-inflammatory cytokines and changes in the functional state of the endothelium. In this article, changes in the level of proinflammatory cytokines and the functional state of the endothelium are studied, as well as the relationship of these changes with comorbid psychoemotional disorders when performing simultaneous surgical interventions by laparoscopic and open methods in combined diseases of organs of the abdominal and anterior abdominal wall. The authors carried out a prospective, randomized controlled study of 586 patients aged 18 to 72 years who underwent planned simultaneous surgical intervention (SSI) with combined diseases of the abdominal cavity, pelvis and anterior abdominal wall. In the course of the comparative analysis, a general trend was established: the simultaneous surgical interventions caused intensification of proinflammatory cytokines and changes in the functional state of the endothelium